DNA hypermethylation regulates the expression of members of the Mu-class glutathione S-transferases and glutathione peroxidases in Barrett's adenocarcinoma. Issue 1 (29th July 2008) - Peng, D F; Razvi, M; Chen, H; Washington, K; Roessner, A; Schneider-Stock, R; El-Rifai, W
Abstract : Background: The accumulation of reactive oxygen species and subsequent oxidative DNA damage underlie the development of Barrett's oesophagus (BO) and its progression to Barrett's dysplasia (BD) and adenocarcinoma (BAC). Methods: The promoter regions of 23 genes of the glutathione S -transferase (GST) and glutathione peroxidase (GPX) families were systematically analysed. Quantitative bisulfite pyrosequencing, real-time RT-PCR, western blot and immunohistochemical (IHC) analysis methods were utilised in this study. Results: 14 genes were identified that have CpG islands around their transcription start sites: GSTs ( GSTM2–M5, GSTA4, GSTP1, GSTZ1, GSTT2, GSTO1 and GSTO2 ) and GPXs ( GPX1, GPX3, GPX4 and GPX7 ). Analysis of an initial set of 20 primary samples demonstrated promoter DNA hypermethylation and mRNA downregulation of GPX3, GPX7, GSTM2, GSTM3 and GSTM5 in more than half of the BAC samples. Further analysis of 159 primary human samples (37 normal, 11 BO, 11 BD and 100 BACs) indicated frequent hypermethylation (⩾10% methylation) of GPX3 (62%), GPX7 (67%), GSTM2 (69.1%) and GSTM3 (15%) in BACs. A significant inverse correlation between DNA methylation and mRNA expression level was shown for GPX3 (p<0.001), GPX7 (p = 0.002), GSTM2 (p<0.001) and GSTM5 (p = 0.01). Treatment of oesophageal cancer cell lines with 5-aza-2′-deoxycytidine and trichostatin-A led to reversal of the methylation pattern and re-expression of these genes at the mRNA and protein levels. The IHC analysis of GPX3, GPX7 and GSTM2 on a tissue microarray that contained 75 BACs with normal squamous oesophageal samples demonstrated an absent to weak staining in tumours (52% for GPX3, 57% for GPX7 and 45% for GSTM2) and a moderate to strong immunostaining in normal samples. Conclusion: Epigenetic inactivation of members of the glutathione pathway can be an important mechanism in Barrett's tumourigenesis.